Dissipative analysis for aircraft flight control systems with randomly occurring uncertainties via non-fragile sampled-data control - Kumar, S. Vimal; Anthoni, S. Marshal; Raja, R. (Mathematics and computers in simulation, 2019)
This work investigates the problem of robust dissipative analysis for aircraft flight control systems via non-fragile sampled-data control approach. The uncertainties occurring in the system parameter is assumed to be random and satisfy the Bernoulli distribution. The main objective of this work is to design a non-fragile sampled-data controller such that the resulting closed-loop system is robustly stochastically stable and strictly (Q,S,R)-α-dissipative. By constructing a suitable augmented Lyapunov–Krasovskii functional (LKF) with Lyapunov stability theory, some sufficient conditions are composed in the structure of linear matrix inequalities (LMIs) and it can be interpreted through some known software collection. Finally, a practical example with simulation is provided to indicate the usefulness of the suggested control design technique. •This is the first attempt to deal the non-fragile sampled-data feedback controller design along with gain fluctuation parameters for aircraft flight control systems.•A more generalized non-fragile sampled-data controller is designed for the proposed aircraft flight control systems subject to randomly occurring uncertainties, input delay, and external disturbance and gain variations.•Based on Lyapunov stability theory with Jensens integral inequality, a new set of sufficient conditions is derived in terms of LMIs to achieve the proposed aircraft flight control system is stochastically stable with a prescribed dissipative performance index.•Finally, we calculated maximum allowable upper bound of time varying delay for special cases namely H∞, passivity, and combined H∞ and passivity which are provided in Table. Moreover, the performances of desired dissipative case and its special case are classified in the numerical simulation part.